2008
DOI: 10.1001/archpsyc.65.7.816
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor 1 Gene Association With Nicotine Dependence

Abstract: Context The endogenous cannabinoid system has been implicated in drug addiction in animal models. The cannabinoid receptor 1 (CNR1) gene is 1 of the 2 receptors expressed in the brain. It has been reported to be associated with alcoholism and multiple drug abuse and dependence. Objective To test the hypothesis that the CNR1 gene is associated with nicotine dependence. Design Genotype-phenotype association study. Ten single-nucleotide polymorphisms were genotyped in the CNR1 gene in 2 independent samples. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 65 publications
(70 reference statements)
2
67
0
Order By: Relevance
“…Several studies have demonstrated nicotine-induced alterations in brain CB 1 receptor expression and function (Gerard et al, 2010;Marco et al, 2007;Werling et al, 2009). Screening of two independent clinical populations revealed that CB 1 gene variants are associated with nicotine dependence (Chen et al, 2008) and the CB 1 receptor antagonist Rimonabant (SR141716A) prolonged abstinence rates in smokers expressing motivation to quit . SR141716A and the related CB 1 antagonist AM251 reduce nicotine selfadministration (SA) by rats (Cohen et al, 2002(Cohen et al, , 2005Forget et al, 2009;Shoaib, 2008), attenuate nicotine-induced increases in nucleus accumbens (NAc) dopamine (DA) (Cheer et al, 2007;Cohen et al, 2002;Grieder et al, 2012), and reduce reinstatement of nicotine-seeking behavior in animal models of relapse (Forget et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated nicotine-induced alterations in brain CB 1 receptor expression and function (Gerard et al, 2010;Marco et al, 2007;Werling et al, 2009). Screening of two independent clinical populations revealed that CB 1 gene variants are associated with nicotine dependence (Chen et al, 2008) and the CB 1 receptor antagonist Rimonabant (SR141716A) prolonged abstinence rates in smokers expressing motivation to quit . SR141716A and the related CB 1 antagonist AM251 reduce nicotine selfadministration (SA) by rats (Cohen et al, 2002(Cohen et al, , 2005Forget et al, 2009;Shoaib, 2008), attenuate nicotine-induced increases in nucleus accumbens (NAc) dopamine (DA) (Cheer et al, 2007;Cohen et al, 2002;Grieder et al, 2012), and reduce reinstatement of nicotine-seeking behavior in animal models of relapse (Forget et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This genetic region has been linked to schizophrenia (Levinson et al, 2000;Leroy et al, 2001), but this has not been replicated, although recently the CNR1 gene has been associated with specific symptoms or with non-responder status for antipsychotic drugs rather than with schizophrenia as a disorder (Chavarria-Siles et al, 2008;Hamdani et al, 2008). There are more convincing results on the association of the CNR1 gene and substance abuse disorders (Zhang et al, 2004;Zuo et al, 2007;Chen et al, 2008), although there is a negative replication study (Herman et al, 2006). Regarding depression, two studies with significantly smaller sample sizes failed to find any association with depression using the (AAT) n polymorphism (Barrero et al, 2005;Tsai et al, 2001), although the former found that a significant association emerged when only the depressed patients with Parkinson's disease were considered (Barrero et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence from pharmacologic and neurochemical studies that the endogenous cannabinoid system is involved in addiction to substance abuse. Of the two known cannabinoid receptors, the receptor which is mainly responsible for neurophysiological and behavioral responses related to addictive behavior is CNR1 35 . The association of three polymorphisms in CNR1 (rs1049353, rs806379, and AAT repeat) with substance dependence has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%